Decorated Pillars of the Rangamandapa - Temples of India Project Team (Jio Institute, 2024)
The pillars of the rangamandapa (open type of pillared hall) feature a variety of motifs which are used to decorate these pillars. The square pillars are adorned with the purnaghata kalasha (vase of plenty), an auspicious decorative motif commonly found in Indian temples. The other motifs include a grassamukha, also known as kirtimukha (face of glory), as well as a leaf and beaded loop motif and a half medallion filled with flowers and birds.